Public knowledge and awareness of tick-borne pathogens and diseases: A cross-sectional study in Ghana - Alale, Theophilus Yaw; Sormunen, Jani J.; Nzeh, Joseph; Agjei, Richard Osei; Vesterinen, Eero J.; Klemola, Tero (Elsevier BV, 2025)
Tick-borne diseases (TBDs) pose a significant and increasing health threat globally. About 45 tick species have been described from Ghana, located in sub-Saharan Africa, but it is unknown how well-informed local citizens are regarding the risks posed by ticks and TBDs. Utilizing a cross-sectional design with questionnaires, this study assessed the public knowledge and awareness of ticks, tick-borne pathogens (TBPs) and TBDs in Ghana. With demographic background data, we received knowledge responses from 537 respondents across all 16 regions of Ghana through an electronic survey and structured interview questionnaire. Descriptive table statistics were used to tabulate frequencies and percentages of all categorical responses and more closely tested for associations between certain variable pairs. Our results showed that 88% of respondents kept at least one animal species irrespective of being a farmer or not. Of all respondents, over 70% (n = 352) were not aware of TBDs in humans while over 50% (n = 289) indicated their awareness of TBDs in animals. Interestingly, we found a significant association between age group and awareness of TBDs in animals. Furthermore, the results highlighted the association between domestic animal ownership and increased human-tick encounters. These findings suggest a need for targeted public education on TBDs in Ghana. As Ghana imports livestock, the risk of TBD spread demands attention. Overall, the survey contributes essential insights for veterinary and public health interventions, stressing the urgency of raising awareness and understanding among the public regarding the risks associated with ticks and TBDs.